Optimalisasi Aset Infrastruktur Perkeretaapian - Sebuah Tinjauan (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Railway infrastructure assets are key components in the railway transportation system. Optimal asset management is essential to improve the efficiency and productivity of the railway system, as well as help prevent unnecessary costs in the asset life cycle. Reliability, Availability, Maintainability, and Safety (RAMS) and Life Cycle Cost (LCC) methods can be used in managing railway infrastructure assets. RAMS is a method used to assess the performance of high-complexity systems such as rail infrastructure systems. In contrast, LCC is used to evaluate the overall cost of a system or asset over the life cycle. Integrating RAMS and LCC concepts can help plan railways' design, operation, and maintenance. This integration is very flexible as it can be done from the life cycle's design, operation, and maintenance stages. Research shows that using the integration of RAMS and LCC can lead to better strategic decisions in the life cycle of a railway. In selecting assets to support design and maintenance, for example, there are two high-speed rail double-track alternatives of ballasted and ballastless track, with results showing that ballastless track has higher RAMS performance and lower maintenance cost but higher construction costs, so ballasted track solutions are preferred for short-term construction and the ballastless track is preferred for long-term.